1997
DOI: 10.1046/j.1471-4159.1997.69041335.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of 2′,3′‐Cyclic‐Nucleotide 3′‐Phosphodiesterase in Vertebrates: cDNA Cloning and Amino Acid Sequences for Chicken and Bullfrog Enzymes

Abstract: Abstract:In mammalian brain, two 2',3'-cyclic-nucleotide 3'-phosphodiesterase (EC 3.1.4.37) isoforms, CNP1 and CNP2, are translated, respectively, from the two mRNAs, which have been transcribed and processed by alternative use of the two transcription start points and by differential splicing. In the present study, the cDNAs encoding chicken CNP2 and bullfrog CNP1, respectively, were isolated, and the amino acid sequences of chicken CNP2 and bullfrog CNP1 were deduced. Western blot analysis showed that chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Mal T-cell differentiation protein (encoded by MAL ) is involved in myelin biogenesis [94]. Finally, 2',3'-cyclic nucleotide 3' phosphodiesterase (encoded by CNP1 ) participates in early oligodendrocyte differentiation and myelination [95-97]. …”
Section: Discussionmentioning
confidence: 99%
“…Mal T-cell differentiation protein (encoded by MAL ) is involved in myelin biogenesis [94]. Finally, 2',3'-cyclic nucleotide 3' phosphodiesterase (encoded by CNP1 ) participates in early oligodendrocyte differentiation and myelination [95-97]. …”
Section: Discussionmentioning
confidence: 99%
“…9 This hypothesis was tested by the generation of several site-directed mutants of zebra fish RICH (zRICH) protein in which amino acid residues of the putative active-site domain (Ser331, Arg332, His334, Thr336, and Cys339) were mutated to alanine. 27 The results showed that no activity was detected for the His334Ala or Thr336Ala mutant, which correspond to His310 and Thr312 in hCNP, respectively, and established that the histidine and threonine residues in the second H-X-T-X motif of 2H phosphoesterases are essential for catalysis.…”
Section: Correlation Between Structural and Functional Datamentioning
confidence: 99%
“…9 CNP catalyzes the hydrolysis of NOp to N-2 0 p in vitro, but the biological function of CNP in vivo remains unknown. Several functional studies have suggested possible functions of CNP.…”
mentioning
confidence: 99%
“…As a solute carrier protein, SLC1A2 is the principal transporter that clears the excitatory neurotransmitter glutamate from the extracellular space at synapses in the central nervous system (60). CNP is expressed exclusively by oligodendrocytes in the CNS, and the appearance of CNP seems to be one of the earliest events of oligodendrocyte differentiation (61). GAD1 encodes one of several forms of glutamic acid decarboxylase, which catalyzed production of gamma-aminobutyric acid (GABA) from Lglutamic acid (62).…”
Section: Developmental Toxicants On Differentiated Es Cellsmentioning
confidence: 99%